Serum level of Interleukin-8 in subjects with diabetes, diabetes plus oral lichen planus, and oral lichen planus: A biochemical study - Atefeh Tavangar; Faezeh Khozeimeh; Fereshtehossadat Ghoreishian; Mahsa Abbasi Boroujeni (Wolters Kluwer Medknow Publications, 2016)
Background: Correlation between diabetes mellitus (DM) and oral lichen planus (OLP) seems probable. Since Interleukin-8 (IL-8) is an important inflammatory mediator involved in both conditions, this study aimed to measure and compare the serum level of IL-8 in DM, OLP, and DM + OLP patients in comparison with healthy individuals. Materials and Methods: This cross sectional study was conducted on 75 patients (30 OLP, 5 OLP and type II DM, 20 type II DM, and 20 healthy controls). Serum levels of IL-8, fasting blood sugar (FBS) and 2-h postprandial blood sugar were measured in the four groups. Data were analyzed using SPSS version 20 by one-way ANOVA and post_hocleast significant difference test. Results: Type II DM patients with OLP had the highest mean serum level of IL-8 followed by OLP, DM and control groups, respectively. Pairwise comparison of groups revealed significant differences in serum IL-8 between the control and OLP and also control and OLP+DM (P < 0.05) groups. No other significant differences were noted. The mean levels of FBS and 2-h postprandial blood sugar were the highest in OLP+DM patients followed by DM, OLP and control groups, respectively. Conclusion: The ascending trend of serum level of IL-8 in the control, DM, OLP, and DM+OLP patients may indicate the role of this factor in the pathogenesis of DM and OLP. Moreover, it may play a synergistic role in patients suffering from both conditions.